Effect of electric current on densification behavior of conductive ceramic powders consolidated by spark plasma sintering. (1st February 2018) - Lee, Geuntak; Olevsky, Eugene A.; Manière, Charles; Maximenko, Andrey; Izhvanov, Oleg; Back, Christina; McKittrick, Joanna
Abstract: The densification mechanism of conductive powders is revealed by comparing the electric current-assisted spark plasma sintering (SPS) of ZrN powder with conventional hot pressing (HP) carried out with the same powder and under the same pressure and temperature. To determine the actual temperature inside ZrN powder, a sacrificial thermocouple is directly inserted into the powder during the SPS process. The spatial distribution of the electric current passing through the powder is calculated using the finite element modeling. The porosity-interparticle neck area geometrical relationship is applied to estimate the electric current density inside the powder volume subjected to SPS. For the first time, by taking into account the explicit influence of the electric current effect on the SPS densification mechanism, the constitutive equations describing the electric current-assisted hot pressing of powders are developed. The densification mechanism of ZrN is determined by the inverse regression of the new SPS constitutive equations and by utilizing the experimental results on ZrN powder consolidation with and without the participation of the electric current effect. Graphical abstract: Image 1